Problemi e prospettive dell’influencer marketing nell’ecosistema digitale (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
Issues and perspectives of influencer marketing in the digital ecosystemThe paper aims to explore the legal implications of influencer marketing and highlight the necessity of adopting rules that specifically address this phenomenon. The article also aims to examine the controversial topic of baby influencers, who are frequently at the core of digital marketing strategies that profit on their data and image. It also examines the issue of virtual influencers in the Metaverse context.
Keywords: Influencer marketing; Data protection; Privacy; GDPR; Metaverse; Sharenting; Kidfluencers; Diritti e libertà fondamentali; Cybersicurezza; Regulation